Efektifitas Teknik Meneran terhadap Robekan Perineum pada Ibu Inpartu Primigravida - Eva Solena Barus; Elvi Era Liesmayani; Christine Novmaren (Jurnal Bidan Mandiri, 2024)
One of the factors influencing how smoothly a birth occurs is knowing when to push. A midwife has to be competent to oversee the childbirth process and experienced in teaching the mother appropriate pushing methods in order to prevent the mother's perineum from being torn and the bleeding that usually follows. The purpose of this study was to ascertain how pushing behaviors affected the incidence of perineal tears in primigravida moms. This study used a quantitative, quasi-experimental one group posttest design. Fifteen primigravida pregnant women made up the research sample of responders, according to the sample calculation formula. Studies employing the paired difference test method (paired sample t-test) shows that the pushing technique is effective in treating perineal tears with a p-value of 0.015. The conclusion of this research is that the meneran technique can be used as an alternative to prevent perineal tears and it is recommended that midwives apply the pushing technique method to inpatient care patients, especially